Estabilidade de métodos numéricos LCR para a simulação de escoamento - Silva, Luciene Aparecida Bielça [UNESP] (2014)
This work focuses on a stability study, using model equations, so that future extensions can be made, as well as testes can be applied directly to the coupled Navier-Stokes equation of a viscoelastic model. Here, however, we restrict ourselves to a highly complicated situation present in this type of problem that is tied to viscoelastic uid, synthesized as a rule, by the number of Weissenberg (We). Thus, the research aims to a stability study, involving LCR in an transport equation model. This will allow to outline the impact of the EVSS formulation in terms of stability in the numerical solution of the momentum equation in the Navier-Stokes when LCR is used or not.